العلاج الأسري في الجزائر - سليمان مسعود, ليلى; معتصم ميمونى, بدرة (جامعة الوادي - University of Eloued, 2020)
ملخص: انطلقت الدراسة من نتائج البحث حول فعالية العلاج الأسري في الجزائر التي تبين من خلالها بأن العملية العلاجية تنطلق من خصوصية الأسرة وثقافتها، حيث هدفت إلى الكشف عن العوامل الخاصة بالأسرة والعوامل الخاصة بالمختص النفسي التي تؤثر في تطبيقه. اعتمدت الباحثة في هذه الدراسة على المنهج الوصفي، إذ قامت بتطبيق استبيان العلاج الأسري الذي بنته بعدما أجرت دراسة خصائصه السيكومترية على عينة مكونة من 118 أسرة في ثلاثة ولايات نموذجية: مستغانم وهران وعين تموشنت. تمت المعالجة الإحصائية عن طريق البرنامج الإحصائي مع الاستعانة بالمتوسط الحسابي والنسبة المئوية لوصف معطيات الدراسة، وبمربع إيتا 2η للوقوف على حجم التأثير. خلصت الدراسة إلى أن تطبيق العلاج الأسري في الجزائر يتأثر بالمستوى التعليمي للأسرة و ليس بمستواها الاقتصادي، كما يتأثر بشكل واسع بالخبرة لدى المختص النفسي، بينما لا يتأثر بإطار العمل. Abstract Our study is based on the results of research on the effectiveness of family therapy in Algeria, which shows that the therapeutic process should be based on the specificity of the Algerian family and its culture. This study aimed to explore the specific family factors and the factors associated with the psychologist that affects its application. We have adopted the descriptive approach and have applied a family therapy questionnaire built by the researcher after studying its psychometric properties on a sample of 118 families in three pilot departments : Mostaganem, Oran and Ain Temouchent;, the researcher has analyzed statistically all the data by SPSS. 20 programmers, using the arithmetic mean and the percentage to describe the data of the study, and the value of Eta square η 2 to determine the magnitude of the effect. The study concluded that the application of family therapy in Algeria is influenced by the educational level of the family not by its economic level, and is also greatly influenced by the experience of the psychologist, and not affected by his framework.
و العوامل المؤثرة في تطبيقه دراسة
مقال
Keywords: علاج أسري ; الجزائر ; الاسرة ; تعليم ; اقتصاد ; خبرة; family therapy, educational level, economic level, therapist experience, framework